Body Shaming in Contemporary Islamic Law: A Comparative Analysis of the Ja’fari Methodology and Al-Ghazali’s Maqashid Approach - Gilang, Rahmat (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2026)
The phenomenon of body shaming on social media demonstrates how digital spaces can give rise to new forms of harassment that impact individuals’ dignity and psychological well-being, calling for a reinterpretation of Islamic law through contemporary ijtihad. This study examines the application of contextual ijtihad in addressing body shaming by comparing the Ja’fari istinbath methodology with Al-Ghazali’s maqashid approach through qualitative research. The findings indicate that the Ja'fari istinbath methodology, which positions reason as the third source of law after the Qur’an and hadith, offers greater scope for formulating legal provisions on digital ethics and social media harassment. Meanwhile, Al-Ghazali’s maqashid approach emphasizes safeguarding the five basic human needs (al-kulliyyat al-khams), particularly hifdz al-nafs and hifdz al-‘aql, directly related to dignity and psychological integrity. Both approaches converge in affirming the urgency of preserving human dignity as a core objective of Sharia. This study concludes that integrating the Ja’fari methodology and Al-Ghazali’s maqashid provides a comprehensive foundation for an Islamic legal response to body shaming, encompassing prevention, victim protection, and behavioral rehabilitation for perpetrators.